A Clinical Study to Evaluate the Effect of Certain Ayurvedic Formulations in the Management of Shwasa Roga w.s.r. to Chronic Obstructive Pulmonary Disease (COPD) - Bhaskar, Anoza; Mehra, B L; Choudhary, Vijay; Bhardwaj, Anil (International Research Journal of Ayurveda & Yoga, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is emerging as a leading cause of death worldwide. It is a disease of old age but genetics and exposure to smoke and fumes of various kinds also make one prone for the development of this disease. In modern medicine various treatment protocols are mentioned but they often have serious side effects. Moreover, this disease has a heterogeneous pattern which means that there are different presentations and different responses to the therapies. So, it is a matter of concern to the scientific world to carry out research works to understand this disease fully and to devise better treatment protocols for the disease. Chronic obstructive pulmonary disease is having similar signs and symptomatology as Shwasa roga described in the Ayurvedic texts. A clinical trial was conducted on 20 patients at R.G.G.P.G. Ayurvedic College Paprola by using classic Ayurvedic formulations namely Kantakari avaleha, Shringyadi churna, Guduchyadi kwatha and Kulathadi kwatha in syrup form. Patients were alternatively divided into two groups of 10 patients each. The Ayurvedic formulations have shown beneficial effects by virtue of their bronchodilator, mucolytic, anti-inflammatory actions for the alleviation of symptoms in the patients of COPD with no untoward effects.